A escola do urbano no campo do município de Catalão/GO : ensino de geografia nas especificidades do lugar - Cláudia Lúcia da Costa (2013)
This study makes an approach to the Morro Agudo Community (Cisterna) located in Catalão city(GO) rural area where stands the Maria Bárbara Sucena Municipal School. This school center is a result of getting together several small and isolated schools, which worked, scattered in many rural communities in the region. After this centralization in a single school, many students had to move along inconvenient distance to get their classes. Morro Agudo Community (Cisterna) was outstanding at garlic cultivation throughout the 1990`s when eventually this activity came to a decline. The region is constituted by properties of small tract of land. The landowners come from a Portuguese background and there are, in addit ion, migrant workers from the northeast region of Brazil. These northeasterners work for these local landowners, and that brings an additional meaning to the social relations in the region and to the rural schooling. The social and cultural diversity of the region has a feedback at the school arising tensions in many ways. In the teaching and learning process the school deals with this diversity, combined with rules and goals that, in the end, delivers a geography teaching not able to value the local knowledge accumulated in the region by its own inhabitants. New methodological approaches to rural school communities emerged out of the analysis of these unmet expectations. Furthermore, this study takes into consideration some “residues”, that means not all events are fit into programs; there are unintended consequences in an open process. All these are object of deep review in this doctoral dissertation. In this community, an analysis of the public policies implemented by Federal and municipal governments to rural schools communities in Brazil was conducted. The way in which public policies toward rural communities are implemented at the schools was reviewed; the goals they pursue and the role played by textbooks are also object of analysis. This study questions the relevance of this tools, mainly if they meet the real needs of the local people. The social representations of teachers and students are considered carefully based on their everyday lives and experiences.